Acceptability and effectiveness of the “Education in Action—ABALL1” intervention program in primary school-aged children - Silva, Isabel S.; Cunha-Saraiva, Filipa; Silvestre, Sandra (Frontiers in Psychology, 2023)
Background: Research has consistently shown the benefits of developing intervention programs in educational settings, enhancing the learning process and socioemotional skills. There is a growing investment in creating and supporting a healthy school environment, prioritizing learning through play. The present study aimed to assess the acceptability and effectiveness of an innovative intervention approach - "Education in Action - ABALL1" - focused on promoting literacy and numeracy skills, and socioemotional competencies of 2nd grade children. Methods: A total of 113 children aged between 7 - 9 participated in the study and were allocated into two groups: intervention (N=69) and control (N=44). The intervention consisted of 24 educational games aligned with the Mathematics and Portuguese curricula, applied for three months, twice a week. Two self-report instruments were used to measure aptitudes for school learning and socioemotional skills, considering two assessment moments: before and after the program implementation. In addition, a focus group involving a subsample of children and teachers who followed the intervention in different school cohorts was carried out. Results: Our results suggested a positive effect of the program concerning children's academic skills, showing a significant improvement in terms of the pre-post-test scores in the intervention group (Cohen’s d= 0.95). Moreover, the qualitative findings also indicate the high acceptability of the program among children and head teachers, who reported a positive effect on the acquisition and consolidation of reading, writing, and arithmetic skills, and on the promotion of teamwork, empathy, autonomy, and self-reflection. Conclusion: Overall, the "Education in Action - ABALL1" program provides a promising intervention based on learning through play directly impacting 2nd grade children's academic, emotional, and interpersonal skills. Further studies are required to understand the transdisciplinary capacity of this intervention approach and its effectiveness at different school levels and curricula.